Art return rates from old master paintings to contemporary art - Federico Etro; Elena Stepanova (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
We study return rates on art investment using a complete dataset on repeated sales for Old Master Paintings, Modern art and Contemporary art auctioned worldwide at Christie's and Sotheby's from 2000 to 2018. We show that return rates do not depend systematically on past prices or the place of sale, but we emphasize substantial differences in returns across sectors. We also control for changes in transaction costs (buyers' premiums and artists' resale rights), characteristics of the sale (evening sales, price guarantees and past bought-ins) and news on the lots (changed attributions, public exhibitions or death of the author) that appear reflected in art returns. We confirm the absence of masterpiece effects in American, Chinese and Ethnic art. Finally, using historical data on prices during Renaissance, Baroque and Neoclassical periods, we find evidence that price changes are independent from initial prices also in the long run.
Keywords: C23; Z11; 330; Art market; Mei-Moses index; Masterpiece effect; Contemporary art